Reconceptualising localised Cold Wars in southern Africa - Mitchell Yates; Drew Cottle (Esboços)
This article aims to examine how localised conditions contributed to the shaping and maintenance of the Cold War in southern Africa during the last three decades of the Cold War. In particular, its focus is on the period 1961 – 1989, during which ‘brushfre’ conficts erupted in the Portuguese colonial territories of Angola and Mozambique, in Rhodesia (and later Zimbabwe), South-West Africa (now Namibia) and the Republic of South Africa. The result of colonisation and decolonisation, racial and ethnic tension and the wider East - West confrontation, the Cold War in southern Africa was never one homogenous confict – evidence strongly attests that it comprised many ‘little Cold Wars’. The forces and governments of the regional states, as well as international powers such as the United States, the USSR, the People’s Republic of China and, most remarkably, communist Cuba, all had clashing geo-political and geo- strategic interests in the southern African region during the last three decades of the Cold War. Their political, economic and military manoeuvring meant that the region played host to some of the most complex localised conficts of the Cold War period. This article will reconceptualise the history of Cold War southern African by demonstrating that, although intrinsically linked, these southern African conficts constituted not one homogenous but several little Cold Wars and that localised conditions were the driving forces for confict, not the wider East-West ideological confrontation.